Guardian : zhen hun. 2 - Priest, 1988- (Guardian: Zhen hun, 2024)
"As snow quietly covers Dragon City in the final days of the lunar year, patients writhing in pain flock to the hospital. Baffled doctors call upon Zhao Yunlan and his team for help. As the case unfolds, Shen Wei and Zhao Yunlan discover that one of the Four Hallowed Artifacts, the Merit Brush, has appeared in the Mortal Realm. In the wrong hands, its power can be transformative. While each step toward the artifact only pulls the pair deeper into a vortex of mysteries, Zhao Yunlan keeps stumbling upon a name: Kunlun. Who is Kunlun, and what is his connection to the Merit Brush? As Zhao Yunlan closes in on the answer, will he also uncover the truth behind Shen Wei's knowing gaze?" --